Confirming the diagnosis of mild hypertension. Issue 6361 (22nd January 1983) - Hartley, R M; Velez, R; Morris, R W; D'Souza, M F; Heller, R F
Abstract : Patients with newly found raised blood pressure are known to have lower pressures at subsequent measurements even when not treated. A study was undertaken to determine the extent to which (a) the number of follow-up measurements and (b) the duration of the intervals between them contributed to this fall in pressure. In 42 general practices 110 patients were identified as having for the first time a diastolic pressure (phase V) greater than 90 and less than 110 mm Hg. Both diastolic and systolic pressures were appreciably lower when measured at return visits when compared with the first measurement. The systolic pressure dropped appreciably in the intervals between the first and the second visits and again between the second and third visits. The diastolic pressure fell appreciably only between the first and second visits. The duration of the interval between visits was not associated with a fall in either systolic or diastolic pressure, but the number of measurements was. This pattern of fall in pressure was not affected by the patient's age or sex. From these results we conclude that patients with newly identified blood pressures that are mildly raised should be seen at two further visits before a decision about treatment is made. The timing of these follow-up visits is not crucial.